PROGRAMMING RADIO BERDASARKAN KARAKTER PENDENGAR PEDESAAN DAN PERKOTAAN (STUDI KASUS DI RADIO PANDOWO TULUNGAGUNG DAN SHE RADIO SURABAYA JAWA TIMUR) - Vinda Maya Setianingrum (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2017)
AbstrakDi era sekarang, meski ada berbagai pilihan media, radio tetap sebagai media alternatif dengan karakteristik pendengar tersendiri. Sifat multitasking radio mengharuskan manajer radio untuk menyediakan program siaran yang menarik bagi pendengarnya. Ini adalah hal yang umum sebagai radio, khususnya radio swasta membuat beberapa perubahan program mereka untuk memenuhi kebutuhan pendengar dan permintaan pasar. Karena konsep segitiga sukses sebuah radio swasta bergantung pada sinkronisasi program dan pendengar, kemudian, berdampak pada pencapaian iklan. Dalam penelitian ini, peneliti menemukan bahwa beberapa radio swasta melakukan perubahan tidak hanya pada program mereka, tetapi juga format dan program radio serta segmen pendengar. Hal tersebut dilakukan oleh She Radio Surabaya dan Radio Pandowo Tulungagung, Jawa Timur. Peneliti menggunakan jenis penelitian kualitatif dan metode studi kasus. Data primer diperoleh melalui wawancara mendalam dengan beberapa informan kunci, yakni direktur program dan manajer dari kedua radio. Dalam proses analisis, peneliti menjelaskan secara kualitatif dengan menggunakan perspektif komunikasi pemasaran. Temuan penelitian menunjukkan bahwa She radio memilih format spesifik perempuan , sementara Pandowo FM menggunakan format budaya.Kata kunci: Radio, format, programing, audiens, She Radio, PandowoAbstractRecently, the various options of media, either printed, television, or, even, internet media, the radio remains as alternative media with its own audience's characteristic. Therefore, the 'multitasking' radio turns the radio's manager to keep up providing interesting broadcasting programs for its listener. It is a common thing as a radio, particularly a private radio makes some changes of their programs in fulfilling the listener and market demand as well. Since the triangle concept of successful in a private radio relies on synchronization of program and listener, then, eventually, impacts on advertising achievement. However, in this research, the researcher finds out that several private radios conducting changing is not only on their program, but also their radio station, format and radio program as well as the listener's segment extremely. Those issues are conducted by She Radio and Radio Pandowo Tulungagung, East Java. Hence, the researcher dissect this case using type of qualitative research and case study method. Therefore, the primary data is gained through in depth interview to several key informants, which is program director and manager of both radios. In addition, the researcher also digs up information from the programmer, broadcaster, music director, marketing, and advertising division as well. In analysis process, the researcher describes qualitatively by using perspective of marketing communication in order to be able finding similarity and difference of both objects. Finally, the research finding shows that She radio turns as female specific formatted radio, while Pandowo FM use cultural formatted radio.Keywords: Radio, format, programing, audiens, She Radio, Pandowo